1995
DOI: 10.1007/bf00019175
|View full text |Cite
|
Sign up to set email alerts
|

A type I element composed of the hexamer (ACGTCA) and octamer (CGCGGATC) motifs plays a role(s) in meristematic expression of a wheat histone H3 gene in transgenic rice plants

Abstract: Type I element (CCACGTCACCGATCCGCG) is a well-conserved regulatory element found in proximal promoter region of a certain class of plant histone genes, that is composed of two independent cis-acting elements of the hexamer (ACGTCA) and the reverse-oriented octamer (GATCCGCG) motifs. To investigate functional role(s) of the type I element in regulation of a wheat histone H3 gene (TH012) promoter activity in vivo, base substitution mutations were introduced into the element and activities of the mutated promoter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
1

Year Published

1995
1995
2000
2000

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 31 publications
0
24
1
Order By: Relevance
“…Nevertheless, we predict that several sequence motifs found in the H2B promoters are cis-acting elements. For example, the type I element, which contributes to the regulation of the meristematic tissue-specific expression of the H3 gene (TH012) promoter [54], is also present in the promoter region of the H2B genes, suggesting that it may also be involved in the H2B gene expression in meristematic tissues. HBP-la (17) can be implicated in the transcriptional regulation of the H2B genes as well because it can bind to the type I element within the H2B promoters (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, we predict that several sequence motifs found in the H2B promoters are cis-acting elements. For example, the type I element, which contributes to the regulation of the meristematic tissue-specific expression of the H3 gene (TH012) promoter [54], is also present in the promoter region of the H2B genes, suggesting that it may also be involved in the H2B gene expression in meristematic tissues. HBP-la (17) can be implicated in the transcriptional regulation of the H2B genes as well because it can bind to the type I element within the H2B promoters (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A characteristic sequence called the type I element (CCACGTCACC-GATCCGCG), which consists of the hexamer motif and the reverse-oriented octamer motif, is conserved in many plant histone gene promoters [30,35,36]. It has recently been demonstrated that the type I element contributes to the regulation of S phase-specific and meristematic tissue-specific expression of the wheat H3 gene (N. Ohtsubo et al,unpublished,[54]). …”
Section: Introductionmentioning
confidence: 99%
“…Such motifs have been collectively referred to as ACGT elements (ACEs, Armstrong et al, 1992;Weisshaar et al, 1991). They have been associated with light regulation of expression of a number of genes encoding proteins associated with photosynthesis (Castresana et al, 1988;Donald and Cashmore, 1990;Giuliano et al, 1988;Meier and Gruissem, 1994) and other light-inducible processes such as flavonoid biosynthesis (Schulze-Lefert et al, 1989), with response to abscisic acid (Marcotte et al, 1989;Mundy et al, 1990;Oeda et al, 1991) auxin (Liu and Lam, 1994) wounding (Rosahl et al, 1986) salicylic acid (Qin et al, 1994;Ulmasov et al, 1994;Zhang and Singh, 1994) and anaerobiosis (DeLisle and Ferl, 1990), and with controlled expression of plant histone genes in relation to cell proliferation (Mikami et al, 1994, Osley, 1991Tabata et al, 1991;Tereda et al, 1993Tereda et al, , 1995Yang et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Two cis elements resembling the GC-rich conserved motifs found in the promoter regions of auxin-regulated genes were shown to be essential for the meristematic tissue-specific activity of the proliferating cell nuclear antigen promoter (Kosugi et al, 1995). Various elements, such as a GC-rich octamer specific to plant histone promoters, a nonamer, and an ATF-related hexameric motif, were shown to be involved in driving specific induction of histone genes in proliferating cells (Terada et al, 1995;Chaubet et al, 1996) and in S phase of synchronized cells (Taoka et al, 1999).In the synchronized BY2 tobacco cell suspension, RNR2 gene expression was shown to increase sharply at the G1/S transition (Philipps et al, 1995;Chabouté et al, 1998). However, the mechanism and the cis elements involved in this induction have remained largely unknown.…”
mentioning
confidence: 99%